Impact of mechanical circulatory support on survival in pediatric heart transplantation. (25th March 2020) - Marcos‐Alonso, Sonia; Gil, Nuria; García‐Guereta, Luis; Albert, Dimpna; Tejero, María Ángeles; Perez‐Villa, Félix; Gómez Bueno, Manuel; Blasco Peiró, Teresa; Cano, Ana; Díaz Molina, Beatriz; Rangel Sousa, Diego
Abstract: Evidence on the impact of MCS on pediatric heart transplant survival is still scarce related to congenital heart disease patients including univentricular physiology as well as the risk factors for complications. We performed a retrospective review of all urgent pediatric (aged ≤16 years) HT from 2004 to 2014 in the Spanish Pediatric Heart Transplant Registry Group. Patients were stratified into two groups: urgent 0 (MCS at HT) and urgent 1 (non‐MCS at HT). The primary outcome measure was post‐transplant survival; secondary outcome measures were complications and absence of infections and rejection during the first post‐transplant year. One hundred twenty‐one pediatric patients underwent urgent HT, 58 (47.9%) urgent 0 and 63 (52%) urgent 1. There were 30 (24.8%) deaths: 12 in the urgent 0 group and 18 in the urgent 1 group, P  = n.s. Regarding the type of MCS, patients on ECMO had the highest rate of complications (80%) and mortality (40%). Patients in the urgent 1 group showed a higher risk of hospital re‐admission for infection during the first year after transplantation (OR 2.31 [1.1‐4.82]), P  = .025. We did not identify a risk factor for mortality. MCS does not impact negatively on survival after HT. However, there is a significant increase in 30‐day and 1‐year mortality and complications in ECMO patients compared with VAD patients. Infants, congenital heart disease, and PediMACS were not found to be risk factors for mortality.